Transformasi Digital Pelayanan Perizinan Berusaha (SI ICE MANDIRI) di Mal Pelayanan Publik Kabupaten Sumedang - Ami Afriyani; Didin Muhafidin; Elisa Susanti (IPB University, 2022)
The use of information and communication technology in governance is a digital governance concept. Online single submission through government regulation number 24 of 2018 as a licensing reform through the concept of implementing digital government. As a response, the Sumedang Regency government underwent a digital-based service transformation through SI ICE MANDIRI. SI ICE MANDIRI as an online-based service system for each licensing and non-licensing at the one-stop integrated investment office. This study uses a descriptive qualitative method through direct observation and interviews with leadership informants, DPMPTSP technical employees, and the community in Sumedang. This study aims to determine and describe the extent of the service transformation process through SI ICE MANDIRI which is integrated with OSS on business permits in the Sumedang Regency environment. The results of this study reveal that SI ICE MANDIRI is still in the development stage, so licensing services are still not optimal. Using the theoretical concept of the Digital Government Maturity Model, it shows that the digital transformation of MANDIRI's SI ICE which is integrated with OSS occupies the integration stage, which means that the business license service process through OSS is carried out through an integrated system between the central government and the regions in various government agencies. Through this service system, the community or business actors carry out the permit process in one stage through the SI ICE MANDIRI and OSS systems.